2022
DOI: 10.21037/jtd-22-93
|View full text |Cite
|
Sign up to set email alerts
|

Immune checkpoint inhibitor-related interstitial lung disease in patients with advanced non-small cell lung cancer: systematic review of characteristics, incidence, risk factors, and management

Abstract: Background: Immune checkpoint inhibitors (ICIs) are widely used in cancers with or without other treatments. Immune-related adverse events (irAEs) have been reported as side effects of ICIs and involve various organs. Pneumonitis, which is also called ICI-related interstitial lung disease (ILD), is one of the lifethreatening adverse events. In this report, we reviewed the safety of ICIs and risk factors for ICI-related ILD in non-small cell lung cancer (NSCLC) patients.Methods: Databases (The National Center f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 72 publications
0
11
0
Order By: Relevance
“…Immunotherapy-related adverse events can affect various organs including lung, skin, endocrine organs, gastrointestinal tract, kidney and others [29][30][31] . Evaluation of risk factors associated with immunotherapy-related adverse events, such as autoimmune diseases, or pre-existing interstitial lung disease is important 32,33 , and checking patients' general conditions before the initiation of the immunotherapy-combined adjuvant treatment is necessary to reduce the possibility of immunotherapy-related adverse events. Since, PORT did not show a definite clinical benefit in the majority of patients who underwent complete resection, radiotherapy-induced toxicity should be an important concern.…”
Section: Safety Issuesmentioning
confidence: 99%
See 1 more Smart Citation
“…Immunotherapy-related adverse events can affect various organs including lung, skin, endocrine organs, gastrointestinal tract, kidney and others [29][30][31] . Evaluation of risk factors associated with immunotherapy-related adverse events, such as autoimmune diseases, or pre-existing interstitial lung disease is important 32,33 , and checking patients' general conditions before the initiation of the immunotherapy-combined adjuvant treatment is necessary to reduce the possibility of immunotherapy-related adverse events. Since, PORT did not show a definite clinical benefit in the majority of patients who underwent complete resection, radiotherapy-induced toxicity should be an important concern.…”
Section: Safety Issuesmentioning
confidence: 99%
“…Immunotherapy-related AEs can affect various organs including the lung, skin, endocrine organs, gastrointestinal tract, kidney, and others [ 29 - 31 ]. Evaluation of risk factors associated with immunotherapy-related AEs, such as autoimmune diseases, or pre-existing interstitial lung disease is important [ 32 , 33 ], and checking patients’ general conditions before the initiation of the immunotherapy-combined adjuvant treatment is necessary to reduce the possibility of immunotherapy-related AEs.…”
Section: Safety Issuesmentioning
confidence: 99%
“…Cancer chemotherapy accounts for 23–51% of drug-induced pneumonia cases, and they are sometimes fatal ( 1 ). Especially, prevalence of immune checkpoint inhibitors (ICI)-related interstitial lung disease (ILD) is reported to be 14.6–19.0% in non-small cell lung cancer ( 2 ). Risk factors are smoking history, pre-existing lung disease, previous drug-induced pneumonia, Eastern Cooperative Oncology Group performance status (ECOG PS) ≥2 at cancer diagnosis, and advanced stage of the underlying cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Since the introduction of ICIs, many studies have been conducted to discover risk factors and to build risk prediction models. Both systematic and non-systematic reviews have been written to identify possible mechanisms for ICI pneumonitis ( 7 ), to summarize risk factors ( 8 ) and to recommend management strategies ( 9 ). A meta-analysis published in 2022 summarized the odds ratios from 35 studies between 2000 and 2022 and identified several risk factors that have significant pooled effect ( Table 1 ) ( 8 ).…”
Section: Introductionmentioning
confidence: 99%
“…Risk of bias analysis has been reported only in one previous review ( 8 ), which, together with other existing reviews, did not provide any detailed assessment on the methodology or the prevalence of bias-prone practices ( 7 , 9 , 13 16 ). Therefore, in the current systematic review, we present a thorough critical appraisal of the methodology of ICI pneumonitis risk factor identification and risk model development studies.…”
Section: Introductionmentioning
confidence: 99%